2017
DOI: 10.1142/s0129183117500462
|View full text |Cite
|
Sign up to set email alerts
|

An improved car-following model from the perspective of driver’s forecast behavior

Abstract: In this paper, a new car-following model considering effect of the driver’s forecast behavior is proposed based on the full velocity difference model (FVDM). Using the new model, we investigate the starting process of the vehicle motion under a traffic signal and find that the delay time of vehicle motion is reduced. Then the stability condition of the new model is derived and the modified Korteweg–de Vries (mKdV) equation is constructed to describe the traffic behavior near the critical point. Numerical simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…More recently, the driver's characteristics have been found to have a significant influence on car-following behavior. Liu et al [28] demonstrated that considering the driver's short-term memory's predictive action could improve traffic flow stability in the car-following behavior. Furthermore, Zhai et al [29] presented an extended continuum model by considering the optimal velocity changes with memory.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the driver's characteristics have been found to have a significant influence on car-following behavior. Liu et al [28] demonstrated that considering the driver's short-term memory's predictive action could improve traffic flow stability in the car-following behavior. Furthermore, Zhai et al [29] presented an extended continuum model by considering the optimal velocity changes with memory.…”
Section: Introductionmentioning
confidence: 99%
“…Car-following theory is one of the most important part of modern traffic theory. Since 1953 when Pipes [1] presented the first model, an increasing number of models have been proposed [2][3][4][5][6][7][8][9].In 2002, Jiang et al [6] presented a car-following model called full velocity difference model (FVDM).FVDM revealed the complex dynamic characteristics of traffic flow, therefore, various developed models based FVDM were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has been an increasing tendency to adopt scientific methods, and try to assess all kinds of traffic phenomena by means of controlled experiments. Paralleled with ex-periments, many physical models have been proposed [1][2][3]. Most of them are hydrodynamic models which provide a macroscopic description of traffic flow.…”
Section: Introductionmentioning
confidence: 99%